Linguistic and socio-pragmatic analysis of nominal treatment formulas in the Colombian Senate - Gómez Gómez, Martha Isabel (Rastros Rostros, 2016)
Introduction: this article presents a linguistic and pragmatic-social analysis of the treatment formulas used in the Colombian Senate. Methodology: a qualitative methodology of exploratory approach was applied. Results: the analysis began with a contextualization of the speech act in political debates, followed by an analysis of the lexical variable from its semantic meaning, emphasizing social variables and discursive strategies, taking in account the approaches made by: Silva, García, Van Dijk, Areiza, Cisneros and Tabares. Conclusions: in terms of morphology, features related to word creation processes were detailed.